Nucleotide Sequence Analysis of the Enteropathogenic Escherichia coli Adherence Factor Plasmid pMAR7 - Brinkley, Carl (American Society for Microbiology, 2006)
The complete nucleotide sequence was determined for pMAR7, an enteropathogenic Escherichia coli (EPEC) adherence factor (EAF) plasmid that contains genes encoding a type IV attachment pilus (Bfp) and the global virulence regulator per. Prototypic EAF plasmid pMAR7 is self-transmissible, unlike the smaller EAF plasmid pB171, which has no genes encoding conjugative functions. The tra locus, a highly conserved 33-kb segment found in pMAR7, is similar to the tra (conjugation) region of the F plasmid. ISEc13 copies flanking the pMAR7 tra region could potentially mobilize or delete the tra genes. Hybridization of 134 EPEC strains showed that a complete tra region is present only in strains of the EPEC1 clonal group. This study confirms EPEC's potential for dissemination of virulence attributes by horizontal transfer of the EAF plasmid.